2021
DOI: 10.3233/jifs-210405
|View full text |Cite
|
Sign up to set email alerts
|

Fault feature extraction method of gear based on optimized minimum entropy deconvolution and accugram

Abstract: Gear fault vibration signals are commonly non-stationary, and useful fault information is often buried in heavy noise, which makes it difficult to extract gear fault features. How to select the suitable fault frequency bands is the key to gear fault diagnosis. To address the above problems, a method combining the improved minimum entropy deconvolution (MED) and accugram, named IMEDA, is proposed for extracting gear fault features. Firstly, a selection index based on permutation entropy (PE) and correlation coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Two filters are constructed by using the boundaries of the level 1 and the highfrequency signal and the low-frequency signal are obtained after filtering. In the same way, three filters are constructed by employing the boundaries of the level 1.6 and the corresponding signals are obtained after filtering [26]. The remaining levels repeat the above steps to obtain the reconstructed signals.…”
Section: Fk Methodsmentioning
confidence: 99%
“…Two filters are constructed by using the boundaries of the level 1 and the highfrequency signal and the low-frequency signal are obtained after filtering. In the same way, three filters are constructed by employing the boundaries of the level 1.6 and the corresponding signals are obtained after filtering [26]. The remaining levels repeat the above steps to obtain the reconstructed signals.…”
Section: Fk Methodsmentioning
confidence: 99%
“…They showed that MED is effective in extracting fault-related impulses. Zhong et al proposed a method combining the improved MED and accugram to extract gear fault features [44]. They used MED to preprocess gear vibration signals and showed the effectiveness of MED.…”
Section: Minimum Entropy Deconvolution (Med)mentioning
confidence: 99%
“…SVM is a classification algorithm that performs nonlinear classification by a kernel method. e core idea of the SVM algorithm is to use mathematical methods to construct the optimal classification surface in the original space or the projected high-dimensional space, so that the given binary categories can be distinguished [11]. e specific procedure is as follows:…”
Section: Classification Recognition Algorithmmentioning
confidence: 99%